The use of aides in a public school articulation therapy program - Gray, Burl B (Journal of All India Institute of Speech and Hearing)
It is not an uncommon experience to find nonprofessionals working in the area of education. These aides (paraprofessionals, sub-professionals supportive personnel, etc., etc.) assist the teacher in the routine classroom activity. In the area of speech pathology, there is not a common utilization of aides. However, in recent years there has been a growing interest within speech pathology concerning the utilization of aides in the direct delivery of speech and hearing services (Alpiner, Ogden and Wiggins,1970, Ptachek, 1967).